2012
DOI: 10.1097/shk.0b013e31824ed57c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Gas on the Survival Rate of Mice Following Global Cerebral Ischemia

Abstract: Global cerebral ischemia and reperfusion (I/R) often result in high mortality. Free radicals have been reported to play an important role in global cerebral I/R, and therefore, reduction of these might improve the outcome. Here, we investigated the effect of hydrogen gas (H2) (a strong free radical scavenger) on the survival rate of mice following global cerebral I/R. We further examined the histopathological outcome and also the brain water content (as a possible determinant of mortality). Male C57BL/6J mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…gas of 1.3% because this is the highest concentration that can be mixed and bottled under high pressure with 30% oxygen for clinical use in Japan (20,27). In contrast, 2.9% hydrogen gas was used in other studies (17,18).…”
Section: █ Conclusionmentioning
confidence: 99%
See 4 more Smart Citations
“…gas of 1.3% because this is the highest concentration that can be mixed and bottled under high pressure with 30% oxygen for clinical use in Japan (20,27). In contrast, 2.9% hydrogen gas was used in other studies (17,18).…”
Section: █ Conclusionmentioning
confidence: 99%
“…Recently, strong clinical and experimental evidence has shown that hydrogen, administered by gas inhalation or ingestion of an aqueous hydrogen-containing solution, has potent protective cellular effects in various diseases (4,5,10,20,21,24,26,27), but without major adverse effects (5). Previous studies have shown that hydrogen has antioxidant, anti-apoptotic, antiinflammatory, and cytoprotective properties that are beneficial to the cell (5).…”
Section: Increasing Evidence Suggests That Reactive Oxygen Speciesmentioning
confidence: 99%
See 3 more Smart Citations